PANDEMI COVID-19 DAMPAKNYA TERHADAP USAHA MIKRO, KECIL DAN MENENGAH DI PASAMAN BARAT - Desda, Mia Muchia; Erdawati, Erdawati (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2021)
This research aims to see the condition of MSMEs in West Pasaman Regency before the COVID-19 pandemic, during the COVID-19 pandemic and during the New Normal period. The research method used a qualitative descriptive approach, with sampling using a sample size technique that is based on the attainment of depth and richness of description. The research and data collection was carried out from October to December 2020, still in the pandemic period and towards the New Normal by collecting primary data with semi-structured interviews. The results showed that prior to the COVID-19 Pandemic, the operational conditions of MSMEs in West Pasaman were still above normal, while at the time of the COVID-19 pandemic, the operational conditions of MSMEs decreased business sales by 75%. And during the New Normal era, the condition of MSMEs was still below normal, because people's purchasing power was still decreasing by 50%.